Interference Efficiency and Effects of Bacterium-mediated RNAi in the Fall Armyworm (Lepidoptera: Noctuidae). Issue 5 (28th September 2021) - Wan, Xiao-Shuang; Shi, Min-Rui; Xu, Jin; Liu, Jian-Hong; Ye, Hui
Abstract: RNAi is an effective tool for gene function analysis and a promising strategy to provide environmentally friendly control approaches for pathogens and pests. Recent studies support the utility of bacterium-mediated RNAi as a cost-effective method for gene function study and a suitable externally applied delivery mechanism for pest control. Here, we developed a bacterium-mediated RNAi system in Spodoptera frugiperda based on four target genes, specifically, Chitinase ( Sf -CHI), Chitin synthase B ( Sf -CHSB), Sugar transporter SWEET1 ( Sf -ST), and Hemolin ( Sf -HEM). RNAi conducted by feeding larvae with bacteria expressing dsRNAs of target genes or injecting pupae and adults with bacterially synthesized dsRNA induced silencing of target genes and resulted in significant negative effects on growth and survival of S. frugiperda . However, RNAi efficiency and effects were variable among different target genes and dsRNA delivery methods. Injection of pupae with dsCHI and dsCHSB induced a significant increase in wing malformation in adults, suggesting that precise regulation of chitin digestion and synthesis is crucial during wing formation. Injection of female moths with dsHEM resulted in lower mating, fecundity, and egg hatching, signifying a critical role of Sf -HEM in the process of egg production and/or embryo development. Our collective results demonstrate that bacterium-mediated RNAi presents an alternative technique for gene function study in S. frugiperda and a potentially effective strategy for control of this pest, and that Sf -CHI, Sf -CHSB, Sf -ST, and Sf -HEM encoding genes can be potent targets.